Gold NanoBeacons for Spectral Codification – Application as a DNA Sensor - Cordeiro, Mílton Jorge Santos (2018)
The use of gold nanoparticles (AuNPs) to develop sensing platforms for the detection of nucleic acids has gained momentum for the past decade. This is due to unique physical properties of AuNPs, such as intense optical modulation, coupled to the possibility of tailoring their reactivity through surface modification. The main objective of this thesis was to develop a biosensor based on the gold nanobeacons technology coupled to wavelength shift mediated by Förster resonance energy transfer (FRET). As a proof-of-concept, the molecular hallmark of Chronic Myeloid Leukemia (CML) - the BCR-ABL fusion gene - was chosen as target. The detection is based on a spectral shift of the donor signal to the acceptor, which allows the corroboration of the hybridization event. The Au-nanobeacon acts as a scaffold for detection of the target in a homogenous format whose output capability (i.e. additional layers of information/NP) is potentiated via the specific FRET signal. To do so, the design of the conventional molecular beacon was changed into a two-component system comprising 1) a donor labeled single-strand DNA with a hairpin structure and 2) an acceptor labeled oligonucleotide that hybridizes to the open state of the hairpin. This system was optimized to allow the specific detection of the fusion sequences and not be triggered by the partial non-fused sequence and, subsequently, hybridize to an acceptor-labeled oligo that identifies which hairpin was triggered in solution. The spectral coded Au-nanobeacons (BioCode) allowed the detection of synthetic pathogenic fusion sequences (with high specificity towards partial complementary sequences), using two distinct fluorescence signals (FRET signal and a partial recovery of the donor emission) over the same hybridization event. Translation of this BioCode strategy to intracellular signaling was also attempted in a theranostic approach. Here, the specific gene silencing and tracking the silencing events via the beacon’s emission. Conceptually, silencing of the enhanced green fluorescence protein (EGFP) mRNA in zebrafish embryos, followed by application to CML cell lines.